Comprehensive metabolomic and microbial analysis of tobacco rhizosphere soil responses to crop rotation and fertilization - Xinyu Liu; Ying Qiao; Xianzhi Wu; Xuanxuan Chen; Fan Yang; Hao Li; Chuanzong Li; Yong Yang; Chunlei Yang; Jun Yu; Pan Luo (Frontiers in Plant Science)
Tobacco (Nicotiana tabacum L.) is a crucial Solanaceae crop globally, but its continuous cultivation can lead to soil degradation. Crop rotation offers numerous benefits, including enhanced soil fertility, improved microbial communities, and pest control. However, how different tobacco planting systems specifically reshape rhizosphere metabolite profiles and regulate microbial diversity remains unclear. Here, we analyzed soil samples from four tobacco cropping systems using non-targeted metabolomics, 16S rRNA and ITS sequencing. The results revealed distinct changes in soil metabolite profiles and microbial communities under different treatments. We identified significant alterations in lipid metabolism, amino acid biosynthesis, and secondary metabolite pathways, which influence soil microbial populations and tobacco plant health. Lipid metabolites, including fatty acids and eicosanoids, were particularly notable for their roles in microbial signaling and plant defense. Furthermore, microbial gene abundance analysis indicated that different treatments fostered unique microbial populations, including increased arbuscular mycorrhizal fungi and saprotrophic fungi, which support nutrient cycling and plant growth. These findings highlight the critical interplay between soil metabolites, microbial diversity, and plant productivity, offering insights into optimizing tobacco cropping systems for improved soil health and sustainable agricultural practices.